2006
DOI: 10.1590/s1413-86702006000100003
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon alfa-2a (40KD) (PEGASYS®) plus ribavirin (COPEGUS®) in retreatment of chronic hepatitis C patients, nonresponders and relapsers to previous conventional interferon plus ribavirin therapy

Abstract: Peginterferon alfa plus ribavirin is currently the treatment of choice for chronic hepatitis C. Peginterferon alfa-2a (40KD) plus ribavirin has given an overall sustained virological response of 18% in F3/F4 previous nonresponder US patients. We evaluated the effectiveness of peginterferon alfa-2a (40KD) plus ribavirin in Brazilian patients who were relapsers or nonresponders to previous interferon-based therapy. One-hundred-thirty-four patients with biopsy-proven chronic hepatitis C, HCV RNA positive, elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
25
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 12 publications
2
25
1
Order By: Relevance
“…Of those, only 17% of the individuals infected with genotype 1, in comparison with 57% of the individuals infected with genotypes 2 or 3, achieved an SVR. Therefore, genotype had an influence on SVR in the previous nonresponders who underwent retreatment.Studies conducted in Brazil and involving nonresponders to IFN/RBV demonstrated SVR rates resulting from retreatment with the PEG-IFN alpha-2a + RBV regimen [10], as well as with the PEG-IFN alpha-2b + RBV regimen [11], that were higher than those reported in international studies. Of the relapsers treated, 57% [10] and 62% [11] achieved an SVR.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…Of those, only 17% of the individuals infected with genotype 1, in comparison with 57% of the individuals infected with genotypes 2 or 3, achieved an SVR. Therefore, genotype had an influence on SVR in the previous nonresponders who underwent retreatment.Studies conducted in Brazil and involving nonresponders to IFN/RBV demonstrated SVR rates resulting from retreatment with the PEG-IFN alpha-2a + RBV regimen [10], as well as with the PEG-IFN alpha-2b + RBV regimen [11], that were higher than those reported in international studies. Of the relapsers treated, 57% [10] and 62% [11] achieved an SVR.…”
mentioning
confidence: 68%
“…Studies conducted in Brazil and involving nonresponders to IFN/RBV demonstrated SVR rates resulting from retreatment with the PEG-IFN alpha-2a + RBV regimen [10], as well as with the PEG-IFN alpha-2b + RBV regimen [11], that were higher than those reported in international studies. Of the relapsers treated, 57% [10] and 62% [11] achieved an SVR.…”
mentioning
confidence: 68%
See 3 more Smart Citations